NABANTINO RAMOS O MODERNIZADOR DA IMPRENSA PAULISTA - Arruda, Laercio Pires de (2007)
Recompiling José Nabantino Ramos life and history track, the objective of this thesis is to showcase and understand his pioneer approach in the modernization of the newspaper complex known as Folhas , as well as to present the value of his contribution to the Brazilian press. To do this, the author adopted the observation approach, analyzing documents, consulting files and libraries, and also oral history, through non-structured interviews. This way it was possible to prove Nabantino Ramos decisively contribution to organize and systemize the Brazilian journalistic process, seeking in the North-American journalism the foundation for the changes introduced in the newspapers from Grupo Folha de S.Paulo.